2014
DOI: 10.5812/ircmj.11798
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing Spondylitis in Iran; Late diagnosis and Its Causes

Abstract: Background:Ankylosing spondylitis (AS) is a chronic destructive and inflammatory disease of the axial skeleton manifested by back pain and progressive stiffness of the spine.Objectives:The aim of the present cross-sectional study was to evaluate and identify factors leading to delayed diagnosis of AS in Iranian patients.Patients and Methods:Sixty patients, (53 males, 7 females) with a diagnosis of AS according to the modified New York criteria were recruited. Diagnosis delay was defined as the interval between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…This could be one of the main reasons for the lower prevalence of AAU in the current study compared to previous ones. Hajialilo et al reported AAU in 6.7% of patients with AS [29], which is a much lower figure than reported in the current study. They further indicated that patients with AAU had the shortest diagnosis delay.…”
Section: Discussioncontrasting
confidence: 86%
“…This could be one of the main reasons for the lower prevalence of AAU in the current study compared to previous ones. Hajialilo et al reported AAU in 6.7% of patients with AS [29], which is a much lower figure than reported in the current study. They further indicated that patients with AAU had the shortest diagnosis delay.…”
Section: Discussioncontrasting
confidence: 86%
“…Delay in diagnosis of SpA has been described in women 5,9,10 and in both sexes 6,7,[11][12][13][14][15][16]20,26,27,29,30,32,33,35,38,39,40,44,45,46 , and although Bandinelli 23 observed less diagnostic delay in women than in men, in most of the papers where delay was compared between men and women, it was greater in women 8,17,18,19,21,22,28,31,34,37,41,42,43,47,48 . This implies that patients have had medically unsolved disorders for a long time, have continued searching for a diagnosis and treatment, or are being erroneously diagnosed and managed 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the main characteristics of the 42 studies on diagnostic delay in SpA included in this systematic review 1,2,3,[8][9][10][11][12][13][14][15][16][17][18]19,20,21,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]48 . The review included 23,883 patients (67.6% men, 32.3% women).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search yielded 1391 citations, from which 21 studies were identified for inclusion after screening [6,35,46,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] (Fig. 1).…”
Section: Study Selection Characteristics and Quality Assessmentmentioning
confidence: 99%